Peculiarities of neuroendocrine and metabolic effects of sulfate-chloride sodium-magnesium mineral waters "Myroslava" and "Khrystyna" of Truskavets' spa in healthy female rats - Myroslava Hrytsak; Dariya Popovych; Nataliya Badiuk; Ivanna Hrytsan (Kazimierz Wielki University, 2021)
Background. Earlier we found that the newly created sulfate-chloride sodium-magnesium drinking mineral waters of Truskavets' spa have similar neuroendocrine and metabolic effects on healthy old female rats significantly different from daily water. The aim of this study is to elucidate the effects of these mineral waters on the neuroendocrine status and metabolism of these animals. Materials and Methods. Experiment was performed on 50 healthy female Wistar rats. Animals of the first group remained intact, using tap water from drinking ad libitum. Rats of the control group for 6 days injected a tap water through the tube at a dose of 1,5 mL/100 g of body mass. The rats of the main groups received the water "Myroslava" and "Khrystyna". The day after the completion of the drinking course in all rats, at first, assessed the state of autonomous regulation by parameters of the HRV. The plasma levels of the hormones of adaptation were determined: corticosterone, triiodothyronine and testosterone (by the ELISA) as well as electrolytes: calcium, magnesium, phosphates, chloride, sodium and potassium; nitric metabolites: creatinine, urea, uric acid, medium molecular polypeptides, bilirubin; lipid peroxidation products and antioxidant enzymes, as well as cholesterol, amylase and glucose. Most of the listed parameters of metabolism were also determined in daily urine. In the adrenals the thickness of glomerular, fascicular, reticular and medullar zones was measured. Results. To identify exactly those parameters, the set of which all four groups of animals differ significantly from each other, the information field of the registered parameters was subjected to discriminant analysis. The program included in the model 8 endocrine and 16 metabolic parameters, information about which is condensed into three roots. The first root reflects directly the SOD and corticosterone and inversely the reticular zone as well as plasma uric acid and glucose. The second root contains information about Nap/Kp ratio, natrihistia, amylasemia, magnesiumuria as well as inversely about kaliemia. The third root reflects directly the triiodothyronine, parathyroid activity, plasma Ca, natriuria and chloriduria as well as urine malondyaldehide. Inversely displays the root information about the testosterone, Ku/Nau ratio, glomerular zone, plasma katalase and Na as well as uricosuria and amylasuria. In the information space of the three discriminant roots, all four groups are quite clearly distinguished. Classification accuracy is 94% (three errors). Conclusion. The newly created sulfate-chloride sodium-magnesium drinking mineral waters of Truskavets resort have specific endocrine and metabolic effects on healthy old female rats with weekly use. This provides a basis for preclinical studies.